Transformation of Literacy Corners in the Development of Deep Learning–Based Inspirational Classrooms in Elementary Schools - Dwi Agus Setiawan; Farida Nur Kumala; Arnelia Dwi Yasa; Sri Rahayu; Siti Halimatus Sakdiyah; Maria Sirvent Gomez (Actual Insight, 2026)
Low student interest in reading and the suboptimal integration of literacy corners into learning remain issues in elementary schools, where literacy corners generally serve only as book storage areas. This community service activity aims to transform literacy corners into part of the development of inspiring deep learning based classrooms to support a culture of literacy in schools. The program was implemented over three months, involving 10 teachers and 100 students from Ngenep 1 and Bumiayu 01 Elementary School, Malang Regency, through a participatory and contextual approach that emphasized the active involvement of teachers and students in each stage of the activity. Program evaluation was conducted using structured observation, reading interest questionnaires, analysis of literacy corner visit frequency, and semi-structured interviews with teachers and students. The evaluation results showed a 75% increase in visits to the literacy corner in three months, from an average of 2.5 times per week before the program to 4.4 times per week after the program, accompanied by a threefold increase in book borrowing in one semester. Qualitatively, students showed more active involvement in reading discussions, learning reflections, and various literacy activities. This indicates that the integration of deep learning-based literacy corners is effective in strengthening literacy culture and creating a meaningful learning environment in elementary schools, thus having the potential to become a model for managing corners.